Foreign Policies and Diplomacies in Asia Changes in Practice, Concepts, and Thinking in a Rising Region - Maass, Matthias (Amsterdam University Press, 2014)
This book offers a variety of perspectives on Asia’s increasing diplomatic prowess, a phenomenon that has accompanied the region’s rapid economic and political development. The editor divides the collection into three broad sections: One group of contributors investigates the regional and international implications of a rising Asia. Another questions whether "Asia" is a useful way to describe several distinct sub-regions. And a third group probes the regional foreign policies of key players across the continent. Together, these contributions point toward areas of potential conflict and collaboration, providing an invaluable resource for diplomats, policy makers, and scholars
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Okt 2018)